Sociolectal and Dialectal Variation in Prosody. (December 2022) - Armstrong, Meghan; Breen, Mara; Gooden, Shelome; Levon, Erez; Yu, Kristine M.
As in many linguistics subfields, studies of prosody have mainly focused on majority languages and dialects and on speakers who hold power in social structures. The goal of this Special Issue is to diversify prosody research in terms of the languages and dialects being investigated, as well as the social structures that influence prosodic variation. The Special Issue brings together prosody researchers and researchers exploring sociological variation in prosody, with a focus on the prosody of marginalized dialects and on prosodic differences based on gender, sexuality, race, and ethnicity. The papers in this volume don't just advance our understanding of critical issues in sociolinguistics, but they also challenge some of the received wisdom in the exploration of sociolinguistic influences on prosody. Not only does this collection highlight the value of this work to informing theories of prosodic variation and change, but the collected papers also provide examples of methodological innovations in the field that will be valuable for all prosody researchers.